Efficacy of interoceptive and embodied rehabilitative training protocol in patients with mild multiple sclerosis: A randomized controlled trial - Paolucci, Teresa; de Sire, Alessandro; Agostini, Francesco; Bernetti, Andrea; Salomè, Angela; Altieri, Marta; Di Piero, Vittorio; Ammendolia, Antonio; Mangone, Massimiliano; Paoloni, Marco (Frontiers in Neurology, 2022)
Introduction The aim of this randomized controlled trial was to evaluate the effect of an embodied rehabilitative protocol, in improving interoceptive awareness respect balance and motor performance in patients with mild multiple sclerosis (pwMS). Methods In this study patients with relapsing-remitting multiple sclerosis were enrolled. The rehabilitative treatment group (TG) participated in an embodied physiotherapy program consisting of 8 one-hour sessions in groups of 4 patients at a time, 1 per week and 2 one-hour sessions of neuro-cognitive exercise in single session during the rehabilitation program. All pwMS underwent a clinical assessment to measure the interoception sense for the Multidimensional Assessment of Interoceptive Awareness scale, balance for the Tinetti Mobility test and stabilometry, quality of life for the Short Form Health Survey-12 and body image perception for Trunk Appearance Perception Scale and Body Image Scale. All previous scales and tests were performed at baseline (T0), at the end of treatment (T1) and after 2 months of follow up (T2). Results Sixty patients were enrolled and randomized into two groups: TG (n = 30), aged 43.0 ± 10.2 years, and a control/waiting list (WLG) group (n = 30), aged 40.7 ± 10.4 years. Statistically significant improvements in interoceptive awareness, body image perception, balance and quality of life were reported in TG versus WLG (p < 0.05). Discussion This study suggests that enhancing interoceptive awareness could improve postural balance. Future studies with a larger sample of patients will be needed to better quantify the effects of an embodied rehabilitation.